EVALUASI UNIT PENGOLAHAN AIR MINUM INSTALASI PDAM RAWA LUMBU 4, BEKASI - Djoko M. Hartono (Purifikasi, 2010)
Public water supply company (PDAM) Rawa Lumbu is a water treatment plant which serves the needs of drinking water in Bekasi with a total production capacity of 260 L/sec. This total production capacity is divided into three smaller units. One of those is steel plate installation with a capacity of 2×100 L/sec, which was built in 2005. As one of drinking water provider, PDAM Rawa Lumbu is demanded to be able to provide safe drinking water that meets national water regulation PERMENKES 907/MENKES/SK/VII/2002. Method of evaluation consisted of 2 step activities. The first step was primary and secondary data collection, site/field observation and discussion with PDAM Rawa Lumbu management for determining existing condition and evaluation stages. The second step was evaluation on treatment plant efficiency in reducing raw water pollutans. Evaluation on the water treatment plant efficiency in reducing water impurities showed that Rawa Lumbu water treatment plant had a good turbidity removal efficiency of 97-99%. Besides, evaluation on unit process dimension with a current flow rate of 68 L/sec and designed flow rate of 100 L/sec, showed that it still had a good performance. However, it performed an actual maximum flow rate of 91 L/sec. The current reservoir can only accommodate a maximum flow rate of 106.41 L/sec.